Primary signet-ring cell carcinoma of the prostate involving the pelvis: a case report - Luo, Shuai; Tian, Xiaoxue; Xu, Ting; Wang, Jinjing (Frontiers in Oncology, 2024)
BackgroundSignet-ring cell carcinoma (SRCC) originates from undifferentiated stem cells in the neck of glands within the lamina propria of the mucosa. Primarily affecting the stomach, SRCC can also involve the breast, pancreas, gallbladder, colon, and bladder, although these cases are rare. SRCC of the prostate is extremely rare, and diagnosing it via pelvic puncture is particularly challenging. Prostate SRCC is a distinct type of malignant tumor characterized by unique biological behavior, high malignancy, rapid disease progression, and poor prognosis. Due to its rarity, early diagnosis and treatment are critical. Currently, the diagnosis and treatment of this disease present significant challenges.Case demonstrationA 74-year-old male patient was admitted to our hospital with “left lower abdominal pain, changes in bowel habits, and bloody stools for 2 months.” A contrast-enhanced pelvic CT scan revealed a soft tissue density mass on the left side of the pelvis. Contrast-enhanced Pelvic MRI suggested a tumor with a rich blood supply on the left side of the pelvis, indistinguishable from the left seminal vesicle and prostate gland, indicating the presence of a suspected malignant tumor. Pathologic biopsy of the pelvic mass confirmed the diagnosis of prostate SRCC. The patient subsequently underwent chemoradiotherapy and has been followed up for three months. He is currently in good condition.ConclusionSRCC predominantly occurs in the digestive tract and rarely originates in the prostate. Diagnosing prostate SRCC through abdominal paracentesis is challenging. To the best of our knowledge, this is the first reported case of SRCC of the prostate initially presenting with gastrointestinal symptoms. Additionally, it presents a case of prostate SRCC involving the pelvis, confirmed through pelvic puncture. highlighting its significance for clinical diagnosis.